PENGEMBANGAN DAN DAYA SAING KOMUNITAS UNGGULAN SEKTOR PERTANIAN KABUPATEN PINRANG - Misbahuddin Misbahuddin (AkMen JURNAL ILMIAH, 2011)
local government policy towards the development and competitiveness of the flagship product that requires support from all of society, the government must also mendukun commodity development in the area in the form of provision of funds, facilities and infrastructure, and financing sources from both banking and non banking institutions.